2013
DOI: 10.1002/jsfa.6472
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for beef potentiator preparation and identification of its characteristic aroma compounds

Abstract: BP prepared by synergistic fermentation with A. oryzae and A. niger is a potential alternative for BP preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Among them, the OAV of furfuryl mercaptan (baking flavor) increased by 5,187,465, methyl 2-methyl-3-furyl disulfide (onion, roast beef) increased by 878,928, 2-Methyl-3-furanthiol (meaty) increased by 295,514, and 1-octen-3-ol (mushroom) increased by 11,066. The sulfur-containing compounds showed the highest OAV, indicating their significant contribution to the overall aroma of the samples due to their lower threshold value ( Gao et al, 2023 ; Gao, Yan, Yang, Lu, & Jin, 2014 ; Ye et al, 2023 ). Furans derived from the Maillard reaction could also be produced via microbial metabolism ( Gao et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the OAV of furfuryl mercaptan (baking flavor) increased by 5,187,465, methyl 2-methyl-3-furyl disulfide (onion, roast beef) increased by 878,928, 2-Methyl-3-furanthiol (meaty) increased by 295,514, and 1-octen-3-ol (mushroom) increased by 11,066. The sulfur-containing compounds showed the highest OAV, indicating their significant contribution to the overall aroma of the samples due to their lower threshold value ( Gao et al, 2023 ; Gao, Yan, Yang, Lu, & Jin, 2014 ; Ye et al, 2023 ). Furans derived from the Maillard reaction could also be produced via microbial metabolism ( Gao et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant amount of odorants, creating the so-called secondary odor, also arises as a result of thermal changes and the activity of microorganisms, as well as due to the use of technological processes during food production [Reineccius (ed.) 2006;Gao et al 2014;Ahhmed et al 2017]. Wang et al [2017] for example, identified in red wine from grapes over seventy volatile substances belonging to: alcohols, esters, terpenic and phenolic compounds, lactones and others.…”
Section: Characteristics Of Aroma Compoundsmentioning
confidence: 99%
“…Beef potentiator was prepared by mincing beef, grinding beef, boiling beef, enzymatic hydrolysis, adding reducing sugar and amino acids and Maillard reaction at 110-130 °C, then auxiliary materials (salt, monosodium glutamate, maltodextrin, preservative, etc.) were added at the end of Maillard reaction, followed by spray drying and packaging [2]. The main production process was shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%